2022
DOI: 10.3390/math10214148
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Correlation Study of Nanofluid Flow Merging Points in Entrance Regions

Abstract: Here, hydrodynamic features of laminar forced nanofluid flow between two parallel plates are numerically investigated, and the results are mathematically discussed. The conventional understanding of developing flow in the entrance region of internal flows is based on the idea that boundary layers start forming at the inlet and merge at some point just before the fully developed section. However, because of the consideration of mass and flow conservation, the entire conception is required to be detailed with ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They preferred DTM for the model results and reported that how several thermophoresis parameters, 5 radiations, magnetic field, and squeeze number alter the model dynamics. The numerical 1 Department of Mathematics, Mohi-ud-Din Islamic University, Nerian Sharif, Trarkhal, Pakistan 2 treatment of the nonlinear fluid model under blowing effects has been analyzed by Mahdavi et al 6 Mahdavi et al 7 isothermal behavior of nanofluid 8 under imposed physical conditions. The nonlinear governing model tackled with the help of ANSYS Fluent 19.3 and simulated the results for the bounded domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They preferred DTM for the model results and reported that how several thermophoresis parameters, 5 radiations, magnetic field, and squeeze number alter the model dynamics. The numerical 1 Department of Mathematics, Mohi-ud-Din Islamic University, Nerian Sharif, Trarkhal, Pakistan 2 treatment of the nonlinear fluid model under blowing effects has been analyzed by Mahdavi et al 6 Mahdavi et al 7 isothermal behavior of nanofluid 8 under imposed physical conditions. The nonlinear governing model tackled with the help of ANSYS Fluent 19.3 and simulated the results for the bounded domain.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdavi et al 7 isothermal behavior of nanofluid 8 under imposed physical conditions. The nonlinear governing model tackled with the help of ANSYS Fluent 19.3 and simulated the results for the bounded domain.…”
Section: Introductionmentioning
confidence: 99%